EFEK ESTROGENIK EKSTRAK DAUN HANDEULEUM {Graptophyllum pictum (L.) Griff)} PADA HISTOLOGI UTERUS MENCIT BETINA OVARIEKTOMI - Listijani Suhargo (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2005)
Estrogenic effects of handeuleum leaf {Graptophyllum pictum (L.)Griff)} were showed by uterus histology examinations of ovariectomy female mice. Female mice aged 3 months, were treated by gavage with handeuleum leaf extracts, ethinyl estradiol, aqua dest, and olive oil. The results showed that the treatment of handeuleum leaf extracts (with concentration 0.5 mg/0.05 ml olive oil) could increase uterus diameter, mucous layer thickness, lumen epithelial cell height, and glandular epithelial cell height if it was compared with aquadest treatments. Compared with ethinyl estradiol as standard estrogen, handeuleum leaf extracts have lower effects than ethinyl estradiol.